Analisis Profil Protein dan Asam Amino Sarang Burung Walet (Collocalia fuchiphaga) Asal Painan - Lina Elfita (Fakultas Farmasi Universitas Andalas, 2014)
This study was aimed to analyze protein profile and amino acid composition of bird nest from Painan, Pesisir Selatan Distric, West Sumatra. Protein analysis was performed by Sodium Dodecyl Sulphate Polyacrilamide Gel Electrophoresis (SDS-PAGE), meanwhile High Performance Liquid Chromatography (HPLC) was used for analysis of amino acid. Analysis on water extract of bird nest by SDS-PAGE showed six bands which correspond to molecular protein which had molecular weight of 147.2; 142.6; 133.4; 73.3; 66.2; and 37.7 kDa, respectively. HPLC analysis demonstrated that bird nest was composed of 16 amino acids. Seven of them were essential amino acids; histidine (2.31%), leucine (3.84%), threonine (3.82%), valine (3.93%), methionine (0.48%), isoleucine (1.80%), phenylalanine (4.49%), and nine of them were non-essential amino acids; serine (4.56%), aspartic acid (4.48%), arginine (3.93%), lysine (2.34%), proline (3.64%), glutamic acid (3.65%), glycine (1.87%), alanine (1.31%), and tyrosine (3.92%). Serine was the highest percentage of amino acid in the bird nest (4.56%), followed by phenylalanine (4.49%) and aspartic acid (4.48%). The study also showed that composition of amino acid in this bird nest was slightly different with composition of amino acid in bird nest from other area.